Analisis Pengendalian Dan Penilaian Persediaan Serta Efisiensi Pemasaran Benih Padi Inbrida Di PT SHS Cabang Lampung - Belliani Belliani; Dyah Aring Hepiana Lestari; Adia Nugraha (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
the aim of this research is to determine the optimal amount of inventory, to analyze the price differences in purchasing inventory and to find out the efficient marketing channels at PT SHS Lampung Branch. The research was conducted at PT SHS Lampung Branch. Data were collected in May-June 2021 using a case study method with primary data and secondary data. Respondents of this research include PT SHS Lampung Branch, distributors and consumers. Data analysis used quantitative descriptive analysis with analytical tools namely Economic Order Quantity (EOQ) and First In First Out (FIFO). Based on the results of the study, the optimal amount of inventory for PT SHS Lampung Branch was 28,091 kg/order. In purchasing raw materials there is no difference in price so there is no problem in determining the value of the materials used. An efficient marketing channel at PT SHS Lampung Branch is a marketing channel with distributors located in Central Lampung and East Lampung.